Erythropoietin protects against renal ischemia/reperfusion injury in rats via inhibition of oxidative stress, inflammation and apoptosis - Alaasam, Elaf R.; Janabi, Ali M. (Journal of Contemporary Medical Sciences, 2023)
Objective: Study investigates erythropoietin's nephroprotective effect in adult male rats with renal ischemia and reperfusion injury, examining biochemical parameters and renal tissue alterations. Methods: twenty-eight male rats of Sprague Dawley randomized into four groups: Sham, Iscemia/Reperfusion, NS, and Erythropoietin. Sham group treated kidneys identically without clamping pedicles. Ischemia/Reperfusion group underwent midline laparotomy, 30 minutes ischemia, 2 hours reperfusion, Rats received NS vehicle for Erythropoietin 30 minutes before ischemia, Erythropoietin dose administered 30 minutes before ischemia/reperfusion. Operation performed under maintained anesthesia using ketamine and xylazine injections. Results: Renal ischemia /reperfusion increased serum Cr, BUN, IL-1β, NF-kB, Caspase-3, while SOD, GSH, Bcl-2 decreased in induced rats. Erythropoietin treatment reduced Cr and BUN levels, Reduced inflammation, and inflammatory markers. Renal tissue antioxidant markers increased; apoptotic markers decreased. Significant increase in Bcl-2 antiapoptotic marker. Erythropoietin-treated group had significantly better renal histological score compared to induced group. Conclusion: Erythropoietin protects against Ischemia/Reperfusion-mediated renal injury, possessing antioxidant, anti-inflammatory, and anti-apoptotic properties.